FACTORS ASSOCIATED WITH CONTRACEPTIVE USE AMONG COUPLES OF CHILDBEARING AGE (PUS) IN THE WORKING AREA OF THE DANAU PARIS HEALTH CENTER, ACEH SINGKIL DISTRICT IN 2023 - Gajah, Yusmawati; Lia Rosa Veronika Sinaga, Lia Rosa Veronika (TOUR HEALTH JOURNAL, 2024)
Background: Population problems faced by developing countries including Indonesia in general are large population, high growth, uneven distribution, and low quality. The problems are very complex and related to each other, resulting in unbalanced population growth. To reduce the rate of population growth can be achieved through the Family Planning (KB) program and the voluntary use of contraceptives to Couples of Fertile Age (PUS) to create effective human resources to improve family resilience, health, safety of mothers, children and women. Purpose: This study aims to determine the relationship between age, education, occupation, knowledge, husband's support, and the role of PLKB with the use of contraceptives in Fertile Age Couples (PUS) in the working area of Danau Paris Health Center, Aceh Singkil Regency in 2023. Method: The type of research used is quantitative research with analytic survey method with cross sectional research design. The sample in this study was taken as many as 92 people who met the inclusion and exclusion criteria. Data collection by distributing questionnaires analyzing the relationship with the chi-square statistical test. Statistical analysis obtained acceptor education (p = 0.011 < 0.05), acceptor knowledge (p = 0.000 < 0.05), acceptor husband support (p = 0.000 < 0.05), and the role of PLKB (p = 0.001 < 0.05) has a relationship with the use of contraceptives, while acceptor age (p = 0.391 > 0.05), and acceptor employment (p = 0.525 > 0.05) has no relationship with the use of contraceptives. Disscusion and Conclusion: It is recommended that the Puskesmas improve the performance of Family Planning Field Officers (PLKB) in conducting family planning education to increase knowledge of contraceptives in the community